Laser Frequency Noise Cancelation in a Phase-Shifted Fiber Bragg Grating Ultrasonic Sensor System Using a Reference Grating Channel - Lingling Hu; Guigen Liu; Yupeng Zhu; Xiangyu Luo; Ming Han (IEEE Photonics Journal)
In an ultrasonic sensor system based on $π$ phase-shifted fiber Bragg gratings $(π\text{FBGs})$ , a cost-effective way for sensor demodulation is to set the laser wavelength at the center of the steep spectral slope of the $π\text{FBG}$ refection spectrum. Frequency noise of the laser source ultimately limits the signal-to-noise ratio (SNR) of the sensor system. Here, we demonstrate a noise cancelation method based on a pair of $π\text{FBGs}$ , which is capable of improving the SNR of system beyond the limitation set by the laser frequency noise. In this method, one of the gratings is used as the sensor to detect the acoustic signal, and the other grating, isolated from the signal, is used as a reference that gives the noise information. Employing a data postprocessing method, the noise is subtracted from the original detected signal. We show that the SNR of the sensor system can be improved by up to 20 dB using this method.